2008
DOI: 10.1093/aje/kwm382
|View full text |Cite
|
Sign up to set email alerts
|

Is Complexity of Work Associated with Risk of Dementia?: The Canadian Study of Health and Aging

Abstract: The authors evaluated the association of complexity of work with data, people, and things with the incidence of dementia, Alzheimer's disease, and vascular dementia in the Canadian Study of Health and Aging, while adjusting for work-related physical activity. The Canadian Study of Health and Aging is a 10-year population study, from 1991 to 2001, of a representative sample of persons aged 65 years or older. Lifetime job history allowed application of complexity scores and classification of work-related physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 46 publications
8
117
2
4
Order By: Relevance
“…Numerous studies found that cognitive activity is associated with a lower risk of dementia even in old age [32][33][34] , and complex intellectually demanding work may have a protective effect [35,36,37] . On the other hand, a number of studies have demonstrated that developmental markers, including height [38,39] , limb length [40] , and head circumference or total intracranial volume as measures of pre-morbid brain size, are related to cognitive impairment and dementia in late life [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies found that cognitive activity is associated with a lower risk of dementia even in old age [32][33][34] , and complex intellectually demanding work may have a protective effect [35,36,37] . On the other hand, a number of studies have demonstrated that developmental markers, including height [38,39] , limb length [40] , and head circumference or total intracranial volume as measures of pre-morbid brain size, are related to cognitive impairment and dementia in late life [41] .…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by findings that engaging in a variety of leisure activities and pursuing an occupation with a high cognitive level lead to enrichment effects, make a contribution to cognitive reserve throughout a person's lifetime, and are related to better cognitive functioning (i.e. better processing speed, memory, and executive functioning) in old age [4,10,11,12,13] (see [14] for a review on enrichment effects in adulthood; see [15] for a recent meta-analysis).…”
Section: Introductionmentioning
confidence: 94%
“…There are a few studies that examined the relationship between cognitive function and work-related physical activity. Kröger et al (2008) fo-cused on work complexity in a 10-year population study with the Canadian Study of Health and Aging 44) which revealed that highly complex work with people or things gave the participant a 28 -64% reduced risk of dementia. In a study on the elderly in Sydney, Australia, Suo et al (2012) found that higher total lifetime experiences are linked with increased grey matter volume in the hippocampus, and supervisory and managerial experience in midlife was the dominant contributor to this effect.…”
Section: Relationship Between Cognitive Function and Physical Activitymentioning
confidence: 99%